The Guidelines for Retirement Savings Motivation among Young Employees: A Case Study of Bangkok - Tongviratskool, Worarpol; Moolsilpa , Poom; Soonsinphai, Thannikan (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
This study aims to investigate personal, financial literacy, and social factors influencing retirement saving behavior among young employees in Bangkok and proposes strategies to enhance saving motivation. A mixed-methods design was used, combining survey data from 400 employees aged 22–29 with in-depth interviews of 10 employees and 6 policymakers or experts. Results show that income, expenses, age, financial literacy, and social context significantly affect saving behavior, with income and financial literacy as the strongest predictors. These findings indicate that income security and financial capability are fundamental determinants of sustainable long-term saving behavior. Qualitative insights highlight that the barriers to saving are systemic rather than purely individual, including constraints at the individual level such as limited income and insufficient financial knowledge; at the organizational level, absence of provident funds and limited financial guidance; and at the policy level, fragmented and uncoordinated measures, especially for informal workers. To overcome these challenges, the study proposes a Whole-of-Society Approach across four dimensions (1) personal, including automatic payroll deductions and financial apps; (2) organizational, including employer matching and auto-enrollment; (3) policy, including a centralized savings agency and tax incentives for low-income groups; and (4) cultural, including campaigns that promote saving norms.